Mondeggi Rigenerazione sociale, culturale e agricola per una Città Metropolitana sostenibile - Biggeri, Mario; De Luca, Giuseppe; Ferrannini, Andrea; Pisano, Carlo (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2023)
The book reports the project for the regeneration of the Villa di Mondeggi Estate elaborated by the Metropolitan City of Florence with the support of the Departments of Architecture and of Science for the Economy and Business of the University of Florence, in implementation of the "Integrated Plans - M5C2 - Investment 2.2" within the framework of the National Recovery and Resilience Plan (NRRP). The project aims to increase the social and economic opportunities of the people who inhabit and will inhabit the entire metropolitan territory, with full respect for the environmental ecosystem and natural resources, with a special focus on young people. The book describes the cooperative governance process introduced to give meaning and design depth to this objective, to become a reference for possible practice of spatial and social regeneration, even beyond the borders of the metropolitan city of Florence.